Armenia and imperial decline - Bournoutian, George A., author.
1 online resource (xxix, 382 pages)
Keywords: Unlike in Tiflis and Baku, the Armenian inhabitants of the Yerevan Province were overwhelmingly peasants. They did not play a major role in the political, intellectual or economic life of the South Caucasus. This book seeks, for the first time, to examine the demography and the social and economic conditions in the Yerevan Province during the first decade of the twentieth century, before the great changes that occurred during World War I and the seven decades of Soviet rule. The aim of the book is to prove conclusively that the Armenians of the Yerevan Province not only benefitted from living under the umbrella of imperial security, but, as junior and senior officials, they also acquired important administrative and professional skills. The social and economic changes of the last decade of Russian rule enabled the local Armenians to advance and, following the collapse of the Russian Empire, to occupy posts previously held by Russians. Thus, despite the absence of their most talented individuals and the lack of experienced political leaders, as well as the loss of half their territory to Turkish attacks in 1918, the local Armenian administration, in the face of terrible conditions and great odds, provided the foundation which allowed the Armenian Republic to maintain its independence until December of 1920. In fact, some of the survivors would assist in the modernization and nation building of Soviet Armenia. Providing a detailed overview of the history of the Yerevan Province in the late imperial age, this book will be a valuable resource for students and scholars interested in the History of Armenia, the Russian Empire and the Caucasus.